PENGAPLIKASIAN JOB SAFETY ANALYSIS (JSA) DAN METODE RAPID UPPER LIMB ASSESSMENT (RULA) PADA PEKERJAAN MANUAL HANDLING - Friska Eka Fitria; Dina Waldani; Wenny Murdina Asih (JURNAL KESEHATAN MERCUSUAR, 2021)
Manual Handling is the process of lifting, moving, placing, pushing, pulling, sliding, and supporting loads with the hands and body. There are 5 work processes at PT. Aura Mandiri Sejahtera still manually which is identified as an ergonomic hazard due to a mismatch between the tool or machine and the posture of the workers. The 5 work processes are the Stone Retrieval Process, the Stone Collection Process, the Stone Lifting Process to the Car Body, the Sand Extraction Process, and the Sand Lifting Process to the Car Body. The purpose of this study was to identify the hazards of manual handling work using JSA and to assess the risks of manual handling work using the RULA method at PT. Aura Mandiri Sejahtera. This type of research is a qualitative descriptive research was conducted from February to August 2021 at PT. Aura Mandiri Sejahtera. The results showed that from 5 manual handling work processes at PT. Aura Mandiri Sejahtera there are 5 ergonomic hazards identified using JSA and when a work risk assessment is carried out using the RULA method, it is found 4 work process with a score of 7 that means efforts must be made to change the work process immediately. for change efforts are expected to the leadership of PT. Aura Mandiri Sejahtera carries out work risk control by modifying work tools in the form of providing or replacing work equipment in accordance with the worker's body posture